Models of teaching - Joyce, Bruce R.; Weil, Marsha (Englewood Cliffs, N.J., Prentice-Hall, 1972)
With the goal of providing the strongest positive effect on student achievement while keeping in line with the current emphasis on standards-based education, Models of Teaching pairs rationale and research with real-world examples and applications to provide a strong foundation for future and new educators. It includes thoroughly documented research on the various models of teaching and their subsequent positive effects on student success. Serving as the core of a successful K-12 teacher education program, Models of Teaching encompasses all of the major psychological and philosophical approaches to teaching and schooling, and gives teachers the tools they need to build strong classrooms that accelerate student learning
Includes bibliographical references.
Keywords: Education -- Experimental methods; Educational innovations; Teaching